舌に複数発生した先天性類表皮囊胞の１例 - 仲宗根, 康成; 小川, 千晴; 狩野, 岳史; 比嘉, 盛敏; 勝藤, 玲奈; 新垣, 敬一 (日本口腔外科学会雑誌, 2025)
In the oral and maxillofacial region, epidermoid cysts most commonly occur in the sublingual floor of the mouth. They are rarely seen initially in the oral region of infants and neonates. In this report, we describe a case of multiple congenital epidermoid cysts in the tongue of a fetus. The patient was delivered via ex-utero intrapartum treatment at 37 weeks and 5 days of gestation. Cystic lesions were detected on the tongue during a fetal ultrasonography, and there was a risk of postnatal airway obstruction. Therefore, the patient underwent endotracheal intubation and was managed in the NICU. CT showed three cystic lesions in the tongue, each measuring 10-20 mm. On the 8th day after birth, the cysts were resected through the midline sagittal glossotomy under general anesthesia. The final histopathological diagnosis was epidermoid cyst. The postoperative course was good with no recurrence. Fetal tongue mass lesions are associated with the risk of airway obstruction and dysphagia, potentially affecting later growth and development. Accurate diagnosis and early treatment in collaboration with related departments are important.